Biomechanical effects of screw orientation and plate profile on tibial condylar valgus osteotomy - Finite-element analysis. Issue 12 (9th September 2020) - Cheng, Chih-Ting; Luo, Chu-An; Chen, Yi-Chih
Abstract: Tibial condylar valgus osteotomy (TCVO) is a type of open wedge high tibial osteotomy for correcting intra-articular deformities of medial knee osteoarthritis. However, there are no implant design and related biomechanical investigations specifically for TCVO. This study aims to investigate the effects of the proximal screw direction and plate profile on the biomechanical behaviors of the TCVO construct. Based on computed tomography images, the tibia model with TCVO was simulated. Four variations (straight and contoured plate profile × convergent and divergent proximal screw direction) with two loading conditions (compressive loads and torsional load) were compared by finite-element method. Fracture risk and construct stability were chosen as the comparison indices. For both loading conditions, the fracture risk of screw, plate and bone was the lowest in straight plate with divergent screw direction (SD), while contoured plate with convergent screw direction (CC) was the highest. Similar results were found in construct stability, SD allowed the smallest micromotions of the L-shaped opening gap, but CC allowed the highest. Divergent screw direction can decrease fracture risk of all components and provide better construct stability, while contoured plate profile seems like to have converse effects. If stability is the major concern, straight plate with divergent screw is recommended for patients with heavy load demands. Contoured plate may be suitable for skinny patients that can reduce the soft tissue irritation.